Commuter mode choice and free car parking, public transportation benefits, showers/lockers, and bike parking at work: Evidence from the Washington, DC region. - Hamre, Andrea; Buehler, Ralph (Univ. of South Florida, 2014)
Municipalities and employers in the U.S. attempt to reduce commuting by automobile through commuter benefits for riding public transportation, walking, or cycling. Many employers provide a combination of benefits, often including free car parking alongside benefits for public transportation, walking, and cycling. This study evaluates the relationship between commuter benefits and mode choice for the commute to work using revealed preference data on 4,630 regular commuters, including information about free car parking, public transportation benefits, showers/lockers, and bike parking at work in the Washington, DC region. Multinomial logistic regression results show that free car parking at work is related to more driving. Commuters offered either public transportation benefits, showers/lockers, or bike parking, but no free car parking, are more likely to either ride public transportation, walk, or cycle to work. The joint provision of benefits for public transportation, walking, and cycling is related to an increased likelihood to commute by all three of these modes and a decreased likelihood of driving. However, the inclusion of free car parking in benefit packages alongside benefits for public transportation, walking, and cycling, seems to offset the effect of these incentives. Benefits for public transportation, walking, and cycling, seem to work best when car parking is not free.
Keywords: Fahrradverkehr; Individualverkehr; Verkehrsmittelwahl; Pendler; Pendlerverkehr; Berufspendler; Berufsverkehr; Alltagsverkehr